2022
DOI: 10.3926/jotse.1341
|View full text |Cite
|
Sign up to set email alerts
|

Socio-critical and problem-oriented approach in environmental issues for students' critical thinking skills development in Chemistry learning

Abstract: This study aims to assess the effectiveness of applying a socio-critical problem-oriented approach in environmental issues to develop students' critical thinking skills in chemistry learning. The qualitative methodology is conducted in which participants critically analyze articles relating to the effect of acids and bases in the environment. Participants are 36 grade 11 chemistry students from a high school in Jakarta, Indonesia. Data are collected by interviews, reflective student journals, teacher notes, ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 24 publications
5
12
0
Order By: Relevance
“…Regarding the first hypothesis, analysis of the results obtained using the statistical method of covariance showed that the strategic training of NLP increased learners' critical thinking. The obtained results are consistent with the results (Biggs, 2003 ; Vieira and Gaspar, 2013 ; Chang et al, 2022 ; Khurana and Lee, 2022 ; Purwanto et al, 2022 ). Critical thinking to learners is considered a new standard of learning skills.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Regarding the first hypothesis, analysis of the results obtained using the statistical method of covariance showed that the strategic training of NLP increased learners' critical thinking. The obtained results are consistent with the results (Biggs, 2003 ; Vieira and Gaspar, 2013 ; Chang et al, 2022 ; Khurana and Lee, 2022 ; Purwanto et al, 2022 ). Critical thinking to learners is considered a new standard of learning skills.…”
Section: Discussionsupporting
confidence: 91%
“…Neurolinguistic programming is a field of psychology that deals with internal processes (Gehlbach and Robinson, 2021 ). Grinder and Bandler developed a new collaborative communication method for language teaching in the early 1970s (Purwanto et al, 2022 ). Neuro, which relates to the nervous system; linguistic, which are words, pictures, and sounds; and programming, which relates to the program to run our thoughts are three elements of NLP (Gran, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Students' lack of critical thinking abilities can be attributed to a lack of instruction in this subject. The findings of this study are relevant to other physical materials research, which indicates that students' critical thinking skills remain low [8,19,20]. Furthermore, the critical thinking skills of each indicator's results are shown in Table 2.…”
Section: Figure 1 Students' Critical Thinking Skills Levelsupporting
confidence: 64%
“…Thus, students engage in learning experiences that facilitate them in developing various skills, including critical thinking. Exploration of student involvement in critical thinking development was analyzed using indicators developed by [10] which are described in detail in the following these sub-chapters.…”
Section: Resultsmentioning
confidence: 99%